2015
DOI: 10.1016/j.dnarep.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

AID expression in B-cell lymphomas causes accumulation of genomic uracil and a distinct AID mutational signature

Abstract: The most common mutations in cancer are C to T transitions, but their origin has remained elusive. Recently, mutational signatures of APOBEC-family cytosine deaminases were identified in many common cancers, suggesting off-target deamination of cytosine to uracil as a common mutagenic mechanism. Here we present evidence from mass spectrometric quantitation of deoxyuridine in DNA that shows significantly higher genomic uracil content in B-cell lymphoma cell lines compared to non-lymphoma cancer cell lines and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 69 publications
4
61
1
Order By: Relevance
“…Both APOBEC and AID have nucleotide preferences in the mutations that they cause. The APOBEC motif was reported as TCW (mutated nucleotide underlined, W = A or T) 39 , while the AID signature is reported as WRCY (Y = C or T) 40,41 . We scanned the nucleotides surrounding the DNMs for the presence of these motifs.…”
Section: Experimental Validationmentioning
confidence: 99%
“…Both APOBEC and AID have nucleotide preferences in the mutations that they cause. The APOBEC motif was reported as TCW (mutated nucleotide underlined, W = A or T) 39 , while the AID signature is reported as WRCY (Y = C or T) 40,41 . We scanned the nucleotides surrounding the DNMs for the presence of these motifs.…”
Section: Experimental Validationmentioning
confidence: 99%
“…Of note, more than half (8 out of 15) of those highly targeted C-to-T and G-to-A mutations lie in a single-stranded DNA-specific AID/APOBEC (apolipoprotein B messenger RNA editing enzyme, catalytic polypeptide-like) cytidine deaminase-targeted motif: 2 of 15 WRCY/RGYW (W 5 A or T, R 5 purine, Y 5 pyrimidine) (Rbms3 and Rab5b); 5 of 15 WRC (Kmt2a/MLL, Adamts2, Tenm3/Odz3, Zcchc2, and Adam34), and 1 of 15 TCW motifs (Slc2a9). 33 These data suggest the involvement of AID activity in the oncogenic transformation of B cells. To confirm this hypothesis, we introduced Tet2 deficiency into an Aicda-deficient background.…”
Section: Tet2 Deficiency Induced Alteration Of Peripheral B-cell Popumentioning
confidence: 80%
“…Our data indicate that Aicda is mainly responsible for those mutations, as is described in CLL and other human B-cell lymphomas, because the frequency of B-cell tumors markedly decrease in Aicda-and Tet2-deficient animals, with respect to Aicda 1/1 Tet2 2/2 animals. However, in addition to AID's function enhancing the ability of antibodies to bind and eliminate pathogens via the mechanism of somatic hypermutation in B cell, several studies in lymphoid and nonlymphoid tissues have demonstrated that AID can also participate in the loss of methylation through its deaminase activity, followed by base excision DNA repair and replacement with unmethylated C. 17,33 Therefore we cannot exclude the possibility that AID could also participate, in the absence of Tet2, in B-cell tumor development via its DNA demethylation function. Pan et al 18 reported phenotypically similar B-cell tumors in 5% of constitutive Tet2-knockout mice and underscored hypermutagenicity in the hematopoietic stem/ progenitor.…”
Section: Discussionmentioning
confidence: 99%
“…AID belongs to the family of APOBEC cytosine deaminases and represents a third source of uracil within the DNA sequence [54]. The DNA cytosine deamination by APOBEC-family enzymes is a natural event in both adaptive and innate immune responses through targeted deamination of Ig genes by AID and deamination of viral DNA by APOBEC enzymes, respectively [55].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent data demonstrate that B-cell lymphoma cell lines contain several-fold increased levels of genomic uracil compared to normal human lymphocytes and non-lymphoma cell lines. Moreover, genomic uracil content correlated with AID protein expression and not with other APOBEC enzymes [54]. Analysis of exome sequencing data from lymphomas and CLL unravelled that these lymphoid malignancies may carry a distinct AID-hotspot mutational signature in kataegis regions, i.e., localized hypermutations in small regions that are also associated with genomic rearrangements [56].…”
Section: Introductionmentioning
confidence: 99%